Realistic modelling of leakage in water distribution pipe networks - Kabaasha, Asaph Mercy (Department of Civil Engineering, 2019)
Several experimental and modelling studies have established that leak areas are mostly not fixed but vary linearly with pressure. Introducing this linear relationship into the orifice equation, results in a two-part modified orifice equation for leakage modelling with pressure head exponents of 0.5 and 1.5 respectively. Current hydraulic network solvers apply the conventional power leakage equation to model pressure dependent demands such as leakage. The empirically derived power leakage equation does not explicitly consider the leak area variation with pressure and it has been found to be flawed under certain conditions. The aim of this study therefore, was to incorporate the modified orifice equation into the algorithm of a hydraulic network solver and evaluate the impact this has on leakage modelling. Epanet is the hydraulic modelling software whose algorithm of the network solver was modified. In addition, a stochastic model for network leak generation and distribution was developed. The conventional and the modified software were applied to different levels of stochastically generated and distributed leakage in three differently sized pipe networks. It was found that the conventional power leakage equation results in significant leakage volume and flow rate errors under certain conditions. A methodology was also developed to correct the conventional power leakage equation so that it can be used to model leakage realistically without a change of the software to one that uses the modified orifice equation. The methodology was thereafter applied to an existing model that detects leaks in standard water distribution pipe networks, and the results showed significant improvements in the performance of the model.